Abdominal Wall Endometriosis: An Overlooked but Possibly Preventable Complication - Chen-Chih Teng; Han-Ming Yang; Kuang-Fa Chen; Chi-Jui Yang; Lien-Sheng Chen; Chuen-Long Kuo (Elsevier, 2008)
Summary: Objective: To find ways of preventing abdominal wall endometriosis through a retrospective case review. Materials and Methods: A retrospective study of 22 patients presenting with 26 postoperative abdominal wall masses. All masses were pathologically proved to be scar endometriosis between September 1994 and September 2006. The age, parity, symptoms and duration, previous surgeries, interval between previous surgery and current operation, initial diagnosis, and the 26 sites and size of endometrioma were recorded and analyzed. Results: About 60% of the patients were in the fourth decade of life. All 22 cases, except one with mid-trimester hysterotomy, had previous cesarean section (CS). Three cases had vertical midline incision for CS, and the other 19 had Pfannenstiel incision, 18 of which were for CS and one for hysterotomy. Of the 22 cases, only three had multiple endometriomas, i.e. one case had three foci and the other two cases had two foci each. Twenty-three endometriomas were found in the Pfannenstiel incision group; 19 out of the 23 foci (82%) were located in either corner of the Pfannenstiel incision wounds (with right side predominance in 13 out of 19). Three endometriomas were noted in vertical midline incisions and two were in the upper corner. Three endometrioma excisions were done during repeated CS. Conclusion: Abdominal wall endometriosis may be caused by iatrogenic inoculation of the endometrium into the surgical wound. It is strongly recommended that, at the conclusion of the surgical procedure, the abdominal wound be cleaned thoroughly, particularly at both corner sites (especially the operator's side). If an abdominal wall endometriosis is encountered after CS but the patient plans to have future pregnancy and the symptoms are mild, excision of the endometrioma may be deferred until the next indicated CS. Key Words: abdominal wall endometrioma, abdominal wall endometriosis, cesarean section, hysterotomy, scar endometriosis